Development of an Application for Document Management in Construction Companies Using Prototyping Method - Sihombing, Denny Jean Cross (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
This research aims to develop a document management application solution in the context of a construction company. Using a prototyping-based software development approach, this research describes the steps from requirements analysis, prototype design, and testing to final evaluation. Testing involved performance, security, and usability tests that proved the quality and effectiveness of the application. The initial post-launch evaluation results showed positive responses from test users regarding ease of use and functionality. Based on the data, 80% of the users found the user interface easy to understand, while 75% indicated a positive level of acceptance towards the app. The main contribution of this research lies in developing an application capable of optimizing document management and operational efficiency in the construction industry. Prospectively, this research provides insights into the potential use of AI and data analytics technologies in future research